Understanding Education of Authoritative Islamic Law Perspective Khaled Abou el Fadl - Mahfud, Choirul (MODELING: Jurnal Program Studi PGMI, 2019)
Problems with Gender-biased Islamic law education and authoritarianism in the United States have invited the anxiety of prominent Muslim intellectual, Khaled Abou El Fadl. In his book on the Speaking in God's Name, Khaled revealed a crucial hermeneutic problem related to the relation of text (text), author (reader). Khaled also revealed the problem of abuse of "authority" in Islamic law that surfaced and was unavoidable among individuals and groups. Evidently, there are a number of religious fatwas not speaking "about God", but acting and speaking "in the name of God". The focus of this paper further discusses what are the hermeneutical problems in Islamic law education discussed by Khaled Abou El Fadl, and what is meant by the issue of authority and abuse, the relation of text-author-reader, and authoritarianism and its implications in the study of Islamic law. Then what are the mechanisms and methods for formulating the right Islamic fatwa.